Evaluation of attributes to hyperbilirubinaemia in neonates in a tertiary care hospital in the Dhaka city (Bangladesh Journal of Medical Science, 2013)
Objective: The study was aimed to evaluate the attributes related to hyperbilirubinaemia among neonates. Materials and methods: A total number of 120 neonates with hyperbilirubinemia included in the study. Data were collected using hospital records and by face-to-face interview of mother of those neonates using a predesigned questionnaire. Data were expressed as mean±SD and number (percent) as appropriate. Both descriptive and inferential statistics were considered in data analysis. Statistical analyses were performed using SPSS Software. Result: Of the total neonates, 57% were baby boys. In age group of 2nd to 7th days were 59.2% of neonates. According to the birth weight, neonates distribution was 38.3% in very low (2500g) birth weight group. ABO incompatibility was found in 14.2% and Rh 8.3% cases of hyperbilirubinaemia. Birth trauma was found in 7.5% and congenital anomalies 3.3% neonates. Pre-maturity (gestational age